FITRAH SEORANG PEREMPUAN TERHADAP KARIR, RUMAH TANGGA DAN PENDIDIKAN - Suryani Jihad (AN-NISA, 2018)
Anatomical and physiological differences also cause differences in selective behavior and ability to intentional activities aimed at and directed at the nature of women themselves. Not to mention the current challenges that require a woman to remain in her nature and wrestle into a career, a household and still have education in managing her household. This can be observed in our surroundings, cities or developing countries regarding the nature of a woman who continues to struggle in her career and does not forget her household and is always required to have education in her expertise, as the main madrasa for her children and not forgetting her religion as a Muslim woman by doing everything according to the teachings of Islam itself.